2006
DOI: 10.1021/jp061582v
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Density Functional Theory Study of the Vibrational Properties of 2-Mercaptobenzimidazole in Interaction with Gold

Abstract: The vibrational properties of the 2-mercaptobenzimidazole (MBI) molecule in interaction with gold were examined by a combined approach of FTIR measurements and density functional theory (DFT). A complete assignment of the 42 normal modes of MBI has been performed on the basis of DFT calculations at the B3PW91 level in complement to the Raman and FTIR spectra. Calculations demonstrated that, on the deprotonated MBI molecule, the negative charge is localized on the sulfur atom, favoring the formation of a gold-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
37
2

Year Published

2009
2009
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 38 publications
(44 citation statements)
references
References 37 publications
(57 reference statements)
4
37
2
Order By: Relevance
“…Raman modes involving the CS bond are visible at 1327 cm −1 (SCN angular deformations – β (SCN)), 1200 cm −1 ( ν (CS) + β (NCN) + δ(NH), and the band at 420 cm −1 can be assigned to C═S stretching ( ν (CS)). The presence of the bands (1200 and 420 cm −1 ) involving C═S stretching suggests a rather thione tautomeric form of the MBI . Further, very weak bands at 1165, 1123, and 1022 cm −1 can be assigned to CH bending (δ(CH)).…”
Section: Resultssupporting
confidence: 60%
See 2 more Smart Citations
“…Raman modes involving the CS bond are visible at 1327 cm −1 (SCN angular deformations – β (SCN)), 1200 cm −1 ( ν (CS) + β (NCN) + δ(NH), and the band at 420 cm −1 can be assigned to C═S stretching ( ν (CS)). The presence of the bands (1200 and 420 cm −1 ) involving C═S stretching suggests a rather thione tautomeric form of the MBI . Further, very weak bands at 1165, 1123, and 1022 cm −1 can be assigned to CH bending (δ(CH)).…”
Section: Resultssupporting
confidence: 60%
“…(a)]. MBI interaction with gold has been studied by Density Functional Theory, Fourier Transform Infrared Spectroscopy (FTIR), and Fourier Transform (FT)‐Raman measurements . On the basis of the published data, the following assignments are possible when using 633‐nm excitation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1-3 Thiols adsorption has also been studied on the other coinage metals [4][5][6][7] . Thiols 4,[8][9][10][11][12][13][14][15] , disulfides [16][17][18][19] , methionines [20][21][22][23][24] , cysteines [25][26][27][28][29][30][31][32][33] , etc. have been studied experimentally and theoretically.…”
Section: Introductionmentioning
confidence: 99%
“…A comprehensive experimental and theoretical investigation showed that many normal modes were significantly affected by deprotonation but barely influenced by the interaction with gold. [66] A related argumentation can be made for CMP. The spectra of protonated (CMP I) and unprotonated (CMP II) cytidine 5'-monophosphate differ because the protonation of the N3 atom results in a modification of the bond lengths, angles, and charge distribution on the pyrimidine ring.…”
mentioning
confidence: 99%